Linking Growth and Liquidity to Firm Value through the Mediation of Profitability - Ardyan Adhijoyo; Danang Prasetya (Journal of Managerial Sciences and Studies, 2025)
This research investigates the influence of growth and liquidity on firm value, emphasizing the mediating role of profitability within food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the period 2020–2024. A purposive sampling method was employed to select 11 representative firms as the research sample. The data were processed using the SPSS application, applying both descriptive statistical analysis and inferential statistical techniques. The findings reveal that: (1) Growth, as represented by asset growth, does not exert a significant influence on firm value. (2) Liquidity, as measured by the current ratio, demonstrates a significant negative impact on firm value. (3) Profitability, proxied by return on assets, effectively mediates the relationship between growth and liquidity on firm value, thereby reinforcing its pivotal role in shaping investor perceptions and firm performance